KUALITAS PELAYANAN PERPUSTAKAAN MELALUI CHAT LAYANAN INFORMASI PERPUSTAKAAN DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Maeni, Ristia Nur (LPPM UNSAP & FISIP UNSAP, 2025)
The Library Information Chat Service is a digital technology-based service innovation implemented by the Archives and Library Office of Sumedang Regency through the WhatsApp application. This service is designed to facilitate users in obtaining information about various library facilities and services. In striving for the success of the Library Information Chat Service, the quality of service is an essential factor. Therefore, the service must operate effectively and efficiently.This study employs a qualitative method with a descriptive analysis approach. Informants were selected using purposive sampling. Data collection techniques included literature study, field study (observation, interviews, and documentation), and triangulation for data validation. Data processing was carried out through data reduction, data display, and conclusion drawing/verification. Based on the results of the study, it can be concluded that the quality of library services through the Library Information Chat Service is considered fairly good. However, there are weaknesses in the tangible and reliability dimensions, which still require improvement. In particular, there is a need for device adjustments and a dedicated server to ensure the service is better structured, more effectively managed, and supported by system stability and service consistency.